Quantum path interferences in high-order harmonic generation - Zair, A; Holler, M; Guandalini, A; Schapper, F; Biegert, J; Gallmann, L; Keller, U; Wyatt, A; Monmayrant, A; Walmsley, I; Cormier, E; Auguste, T; et al. (APS, 2008)
We have investigated the intensity dependence of high-order harmonic generation in argon when the two shortest quantum paths contribute to the harmonic emission. For the first time to our knowledge, experimental conditions were found to clearly observe interference between these two quantum paths that are in excellent agreement with theoretical predictions. This result is a first step towards the direct experimental characterization of the full single-atom dipole moment and demonstrates an unprecedented accuracy of quantum path control on an attosecond time scale.